Factors That Influence Purchase Interest in Shopee Live Using the Technology Acceptance Model Approach - Lombu, Pinus Hardin; Setiyati, Ritta (Yayasan Gema Bina Nusantara, 2025)
Sales through live streaming on the Shopee Live platform have been rapidly growing. Shopee Live provides shopping convenience where consumers can interact directly with sellers. This study aims to identify and analyze the influence of user interface, trust, perceived ease of use, and perceived usefulness on consumers’ purchase intention on Shopee Live. The analytical method used in this study is multiple linear regression using statistical software. The population in this study consists of Shopee users in the Tangerang City area who have watched and made purchases on Shopee Live. The selection of respondents was carried out using a non-probability sampling method with a total of 150 respondents. Based on the analysis results, it is shown that the variables of User Interface, Trust, Perceived Ease of Use, and Perceived Usefulness simultaneously have a positive and significant effect on purchase decisions on Shopee Live. Partially, the user interface does not have an effect on purchase intention on Shopee Live. Trust, Perceived Ease of Use, and Perceived Usefulness have a positive and significant influence on purchase intention on Shopee Live. Furthermore, the analysis results indicate that trust is the most influential variable.